The effect of elevational gradient on Potentilla fruticosa from Pir Panjal range of Jammu &Kashmir, India - Farzana Kouser; Gurdev Chand; Bhav Kumar Sinha; Nazia Parveen; Sapalika Dogra; Muneeba Banoo; Marvi Sharma; Monika Kumari (The Bioscan, 2025)
There is significant interest in understanding how medicinal plants vary in morphological and physiological responses with changes in elevation. And to assess the soil properties of these altitudinal gradients. The mountainous areas of Pir Panjal range of Jammu region offer a unique opportunity to study how plants adapt to rapid changes in elevation. This study focused on Potentilla fructicosa examining their responses at three different elevations of Pir Panjal range of Jammu region: 930 m, 1183 m, and 1843 m above sea level (ASL). In the current study, several parameters have been evaluated along this vertical gradient, including soil physio-chemical parameter along with morpho-physiological parameters (Plant height, leaf area and photosynthetic pigments). The results revealed a negative correlation between soil pH, phosphorus and potassium with increasing altitude. Further, a positive correlation was found between soil total nitrogen, organic carbon, and soil organic matter. The results indicated that with increasing elevation, plant height and leaf area decrease, while photosynthetic pigments increase. Additionally, it was observed that the variations in photosynthetic pigments, leaf area, and plant height in Potentilla fruticosa are attributed to local adaptation. These findings offer valuable insights into how a narrow elevational gradient influences plant morphology and physiology.